Beyond method: The diatribe between Feyerabend and Popper over the foundations of quantum mechanics - Del Santo, Flavio (arXiv.org, 2021)
Karl Popper and Paul Feyerabend have been among the most influential philosophers of science of the twentieth century. Extensive studies have been dedicated to the development of their controversial relationship, which saw Feyerabend turning from a student and supporter of Popper to one of his harshest critics. Yet, it is not as well known that the rift between Popper and Feyerabend generated mainly in the context of their studies on the foundation of quantum mechanics, which has been the main subject of their discussions for about two decades. This paper reconstructs in detail their diatribe over the foundations of quantum mechanics, emphasizing also the major role that their personal relationship played in their distancing.